PENGARUH PEMBERIAN KOMPOS SAMPAH KOTA DAN UREA, TSP, KCL PADA REGOSOL TERHADAP SERAPAN HARA N, P, K, TANAMAN SELADA ( Lactuca sativa L ) - Asmar Asmar; Irwan Darfis (Jurnal Solum, 2009)
A research about Effect of compost as well as Urea, TSP, and KCl fertilizer application in Regosol on nutrient N, P, K uptake by lettuce (Lactuca sativa, L), had been conducted from April to November 2008 in Glasshouse, agriculture Faculty Andalas University Padang.  The objective of the research was to determine the effects of organic fertilizer (compost of market waste) appication and the best NPK fertilizer dossages on soil chemical properties of Regosol planted by lettuce.  This research was a pot trial by using factorial design which was allocated as completely randomized in Glasshouse.  There were two factors, 4 x 4 treatments tested in this experiment, with 3 replications.  The first factor was dossage of compost {K0 = Without compost, K1 = 2,5 ton/ha (10 g/pot), K2 = 5 ton/ha (20 g/pot), K3 = 10 ton/ha (40 g/pot)} and the second factor was NPK dossage (P0 = Without NPK, P1 = 25 % NPK recommendation, P2 = 50 % NPK recommendation, P3 = 100 % NPK recommendation).  The data of this research were tested by using F-test at 5% level, and then continued by using HSD test.  The results showed that application of 10 ton compost / ha could gave the highest pH value, total N, available P, CEC, Ca-exch, Mg-exch, K-exch, and  Na-exch, but decreased Org-C of the soil.  In general, the best interaction of both treatments was found under combination of 5 ton compost/ha and 25% NPK recommendation for plant growth, plant dry matter, and NPK uptake by plants.  Based on the research conducted, it was suggested that the best input for lettuce grown on Regosol was combination between 5 ton compost/ha and 25% NPK recommendation for the plants.Key Words: Compost, Regosol, Lettuce